Isolation of Microorganisms and Its Application for Decolorization of Anthraquinone and Azo Dyes from Textile Wastewater - Fathoni, Ahmad; Jeong, Soo Kyoung; Kim, Joong Kyun (ANNALES BOGORIENSES, 2013)
The treatments of textile wastewater by chemical and physical methods have some drawbacks such as economically feasible and high cost, lack of effective color reduction and formation of by-product. Conversely, biological processes have been proposed as a less expensive and less environmentally intrusive alternative. In the present study, decolorization of various dyes was studied using microorganisms isolated from textile/dye wastewater inoculated into culture medium supplemented with 0.01% of anthraquinone and azo dyes (Disperse Red 73, Lanasol Blue 3G Disperse Orange 30, Kemachrome Black T, and Mixture of dyes). The effect of medium composition was investigated by applying four different media (BSM, ME, Basal, and GYP). From 42 isolates, 4 isolates showed the potential for decolorizing structurally different anthraquinone and azo dyes employed in the industry. Based on the microscopic observation, the 3 isolates designated as OW1, RW8, ATSN-3 were identified as bacteria and 1 isolate designated as BSS was observed as fungus. BSS fungus isolate showed the highest ability to decolorize various reactive dyes including anthraquinone and azo dyes. BSS grew well in the ME medium, resulting in approximately 96.4% decolorization efficiency after 72 hours. The result indicates the potential for this isolate to be used in the biological treatment of textile industry.